Financial Management in the ESG Context: A Bibliometric Review and Author Network Analysis - Judijanto, Loso (West Science Business and Management, 2025)
This study presents a comprehensive bibliometric review and author network analysis of scholarly literature on financial management within the context of Environmental, Social, and Governance (ESG) principles. Utilizing data from the Scopus database and VOSviewer software, the analysis maps the intellectual structure, thematic evolution, and collaborative patterns of publications from 2000 to 2025. The findings reveal that core concepts such as sustainability, corporate social responsibility, ESG performance, and financial performance dominate the research landscape. Emerging themes, including green finance, climate risk, and stakeholder engagement, indicate a growing interdisciplinary interest and the expansion of ESG-related financial strategies. Author and institutional co-authorship networks highlight fragmented yet globally distributed collaboration, with China, the United States, and the United Kingdom playing central roles in knowledge production. This study provides critical insights for researchers, practitioners, and policymakers, while also identifying theoretical gaps and future research directions in the integration of ESG into financial management practices.
Keywords: ESG; Financial Management; Sustainability; Corporate Social Responsibility; Green Finance; Bibliometric Analysis